Prevalence and Therapy Rates for Stuttering, Cluttering, and Developmental Disorders of Speech and Language: Evaluation of German Health Insurance Data - Sommer, Martin; Waltersbacher, Andrea; Schlotmann, Andreas; Schröder, Helmut; Strzelczyk, Adam (Frontiers in Human Neuroscience, 2021)
Purpose: To evaluate the prevalence and treatment patterns of speech and language disorders in Germany. Methods: A retrospective analysis of data collected from 32% of the German population, insured by the statutory German health insurance (AOK, Local Health Care Funds). We used The International Statistical Classification of Diseases and Related Health Problems, 10th revision, German Modification (ICD-10 GM) codes for stuttering (F98.5), cluttering (F98.6), and developmental disorders of speech and language (F80) to identify prevalent and newly diagnosed cases each year. Prescription and speech therapy reimbursement data were used to evaluate treatment patterns. Results: In 2017, 27,977 patients of all ages were diagnosed with stuttering (21,045 males, 75%; 6,932 females, 25%). Stuttering prevalence peaks at age 5 years (boys, 0.89%; girls, 0.40%). Cluttering was diagnosed in 1,800 patients of all ages (1,287 males, 71.5%; 513 females, 28.5%). Developmental disorders of speech and language were identified in 555,774 AOK-insurants (61.2% males; 38.8% females). Treatment data indicate a substantial proportion newly diagnosed stuttering individuals receive treatment (up to 45% of 6-year-old patients), with slightly fewer than 20 sessions per year, on average. We confirmed a previous study showing increased rates of atopic disorders and neurological and psychiatric comorbidities in individuals with stuttering, cluttering, and developmental disorders of speech and language. Conclusion: This is the first nationwide study using health insurance data to analyze the prevalence and newly diagnosed cases of a speech and language disorder. Prevalence and gender ratio data were consistent with the international literature. The crude prevalence of developmental disorders of speech and language increased from 2015 to 2018, whereas the crude prevalence for stuttering remained stable. For cluttering, the numbers were too low to draw reliable conclusions. Proportional treatment allocation for stuttering peaked at six years of age, which is the school entrance year, and is later than the prevalence peak of stuttering.